2014
DOI: 10.1371/journal.pone.0097070
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Novel Action of Thymidine Phosphorylase in Non-Small Cell Lung Cancer: Crosstalk with Nrf2 and HO-1

Abstract: Proangiogenic enzyme thymidine phosphorylase (TP) is a promising target for anticancer therapy, yet its action in non-small cell lung carcinoma (NSCLC) is not fully understood. To elucidate its role in NSCLC tumor growth, NCI-H292 lung mucoepidermoid carcinoma cells and endothelial cells were engineered to overexpress TP by viral vector transduction. NSCLC cells with altered expression of transcription factor Nrf2 or its target gene heme oxygenase-1 (HO-1) were used to study the regulation of TP and the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Cells generate a defensive, protective response against external environmental stimuli by inducing HO-1 expression (Wang et al, 2014a), making HO-1 a potential promoting factor for the growth of lung cancer, liver cancer, malignant glioma, and other tumor cells (Zou et al, 2011;Tertil et al, 2014). We previously reported that inducing HO-1 expression by hemin elevated the survival rate of chronic myelocytic leukemia cells, indicating that HO-1 and the survival of such cells were closely associated.…”
Section: Discussionmentioning
confidence: 99%
“…Cells generate a defensive, protective response against external environmental stimuli by inducing HO-1 expression (Wang et al, 2014a), making HO-1 a potential promoting factor for the growth of lung cancer, liver cancer, malignant glioma, and other tumor cells (Zou et al, 2011;Tertil et al, 2014). We previously reported that inducing HO-1 expression by hemin elevated the survival rate of chronic myelocytic leukemia cells, indicating that HO-1 and the survival of such cells were closely associated.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of VEGF expression by CO is linked to the activation of hypoxia inducible factor-1 (HIF-1α) [57], the effect which might be also responsible for the synthesis of transforming growth factor-β (TGF-β) [58]. The role of other proangiogenic enzyme, thymidine phosphorylase in HO-1 mediated angiogenesis has been also suggested [59,60].…”
Section: Ho-1/co and Angiogenesismentioning
confidence: 99%
“…NCI-H292 cell lines overexpressing NFE2L2 or HMOX1 were developed earlier in our laboratory as described in [14] and [9], respectively.…”
Section: Cell Culturementioning
confidence: 99%